Development and validation of a soft robotic exosuit for assistance of the upper limbs - Xiloyannis, Michele (2019)
Robots have been used in physical rehabilitation to increase the intensity of practice and relieve therapists from the demanding task of manually assisting the patient. Robot-assisted therapy has shown encouraging results, comparable to the ones achieved with traditional therapy, while allowing greater patient compliance and a quantitative, more accurate monitoring of the subject’s performance. Unfortunately, currently available robotic platforms are not logistically capable of following the patient after discharge from physical therapy. Patients go back home, training stops and their conditions plateau or even deteriorate.